Anterior hippocampal volume predicts affect-focused psychotherapy outcome. Issue 3 (18th February 2020) - Suarez-Jimenez, Benjamin; Zhu, Xi; Lazarov, Amit; Mann, J. John; Schneier, Franklin; Gerber, Andrew; Barber, Jacques P.; Chambless, Dianne L.; Neria, Yuval; Milrod, Barbara; Markowitz, John C.
Abstract: Background: The hippocampus plays an important role in psychopathology and treatment outcome. While posterior hippocampus (PH) may be crucial for the learning process that exposure-based treatments require, affect-focused treatments might preferentially engage anterior hippocampus (AH). Previous studies have distinguished the different functions of these hippocampal sub-regions in memory, learning, and emotional processes, but not in treatment outcome. Examining two independent clinical trials, we hypothesized that anterior hippocampal volume would predict outcome of affect-focused treatment outcome [Interpersonal Psychotherapy (IPT); Panic-Focused Psychodynamic Psychotherapy (PFPP)], whereas posterior hippocampal volume would predict exposure-based treatment outcome [Prolonged Exposure (PE); Cognitive Behavioral Therapy (CBT); Applied Relaxation Training (ART)]. Methods: Thirty-five patients with posttraumatic stress disorder (PTSD) and 24 with panic disorder (PD) underwent structural magnetic resonance imaging (MRI) before randomization to affect-focused (IPT for PTSD; PFPP for PD) or exposure-based treatments (PE for PTSD; CBT or ART for PD). AH and PH volume were regressed with clinical outcome changes. Results: Baseline whole hippocampal volume did not predict post-treatment clinical severity scores in any treatment. For affect-focused treatments, but not exposure-based treatments, anterior hippocampal volume predicted clinical improvement. Smaller AH correlated with greater affect-focused treatment improvement. Posterior hippocampal volume did not predict treatment outcome. Conclusions: This is the first study to explore associations between hippocampal volume sub-regions and treatment outcome in PTSD and PD. Convergent results suggest that affect-focused treatment may influence the clinical outcome through the 'limbic' AH, whereas exposure-based treatments do not. These preliminary, theory-congruent, therapeutic findings require replication in a larger clinical trial.